2022
DOI: 10.1186/s12870-022-03909-x
|View full text |Cite
|
Sign up to set email alerts
|

Different color regulation mechanism in willow barks determined using integrated metabolomics and transcriptomics analyses

Abstract: Background The rich yellow-orange to vividly deep red bark of willow (Salix spp.) branches have high ornamental and economic value. However, the mechanism underlying the regulation of willow branch color remains unknown. Therefore, we performed metabolomics and transcriptomics analyses of purple, green, and red willow barks to elucidating the mechanisms regulating color development. Results Seven anthocyanins were isolated; pelargonidin, petunidin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Notably, we also observed the downregulation of two key anthocyanin-induced genes in the OE lines compared to the WT lines (Fig. S6a and b in Additional File 1 ), indicating suppressed anthocyanin synthesis in the OE plants, which represented an opposing trend to Chl accumulation [ 50 , 51 ]. In addition, KEGG pathway enrichment also showed that some DEGs were closely associated with MAPK signaling and plant-pathogen interaction (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, we also observed the downregulation of two key anthocyanin-induced genes in the OE lines compared to the WT lines (Fig. S6a and b in Additional File 1 ), indicating suppressed anthocyanin synthesis in the OE plants, which represented an opposing trend to Chl accumulation [ 50 , 51 ]. In addition, KEGG pathway enrichment also showed that some DEGs were closely associated with MAPK signaling and plant-pathogen interaction (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Anthocyanin synthase (ANS) and BZ1 (Bronze 1) are the last two enzymes involved in anthocyanins biosynthesis, which catalyze the conversion of leucoanthocyanidin to anthocyanidins and then the glycosylation of anthocyanidins (Feng et al 2021; Wilmouth et al 2002). Coexpression of gene ANS and BZ1 were observed in plants and positively associated with the biosynthesis of flavonoid/anthocyanin (Zhou et al 2022; Liu et al 2022b); moreover, the other genes involved in flavonoids biosynthesis (such as genes encoding PAL, C4H, CHS, F3H, ANR, F3’Hs, DFRs, LAR, GT1, etc.) were also significantly upregulated (Liu et al 2022b), suggesting a de novo biosynthesis of flavonoids and anthocyanins in duckweed variety.…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of gene ANS and BZ1 were observed in plants and positively associated with the biosynthesis of flavonoid/anthocyanin (Zhou et al 2022;Liu et al 2022b); moreover, the other genes involved in flavonoids biosynthesis (such as genes encoding PAL, C4H, CHS, F3H, ANR, F3'Hs, DFRs, LAR, GT1, etc.) were also significantly upregulated (Liu et al 2022b), suggesting a de novo biosynthesis of flavonoids and anthocyanins in duckweed variety.…”
Section: Sunlight Exposure Changes the Accumulation And Metabolic Flu...mentioning
confidence: 99%
“…Astaxanthins are carotenoids with high pharmaceutical importance synthesized by ketolase and beta-carotene 3-hydroxylase enzymes from β-carotene [42]. Importantly, beta-carotene 3-hydroxylase and other related enzymes are responsible for ratelimiting steps in β-carotene catalysis [43]. Therefore, the cumin novel miRNA cci-miRN2-3p could represent a key regulator in astaxanthins biosynthesis.…”
Section: Discussionmentioning
confidence: 99%